Individual‐level drivers of dietary behaviour in adolescents and women through the reproductive life course in urban Ghana: A Photovoice study - Julia Liguori; Rebecca Pradeilles; Amos Laar; Francis Zotor; Akua Tandoh; Senam Klomegah; Hibbah A. Osei‐Kwasi; Agnès Le Port; Nicolas Bricas; Richmond Aryeetey; Robert Akparibo; Paula Griffiths; et al. (Wiley, 2022)
Abstract Evidence on the individual‐level drivers of dietary behaviours in deprived urban contexts in Africa is limited. Understanding how to best inform the development and delivery of interventions to promote healthy dietary behaviours is needed. As noncommunicable diseases account for over 40% of deaths in Ghana, the country has reached an advanced stage of nutrition transition. The aim of this study was to identify individual‐level factors (biological, demographic, cognitive, practices) influencing dietary behaviours among adolescent girls and women at different stages of the reproductive life course in urban Ghana with the goal of building evidence to improve targeted interventions. Qualitative Photovoice interviews (n = 64) were conducted in two urban neighbourhoods in Accra and Ho with adolescent girls (13-14 years) and women of reproductive age (15-49 years). Data analysis was both theory‐ and data‐driven to allow for emerging themes. Thirty‐seven factors, across four domains within the individual‐level, were identified as having an influence on dietary behaviours: biological (n = 5), demographic (n = 8), cognitions (n = 13) and practices (n = 11). Several factors emerged as facilitators or barriers to healthy eating, with income/wealth (demographic); nutrition knowledge/preferences/risk perception (cognitions); and cooking skills/eating at home/time constraints (practices) emerging most frequently. Pregnancy/lactating status (biological) influenced dietary behaviours mainly through medical advice, awareness and willingness to eat foods to support foetal/infant growth and development. Many of these factors were intertwined with the wider food environment, especially concerns about the cost of food and food safety, suggesting that interventions need to account for individual‐level as well as wider environmental drivers of dietary behaviours.